Wali Adhal Serta Hubunganya Dengan Konsep Kafāah - Hafidz Miftahuddin, Abdul; Wahid, Abdurrohman (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2021)
The necessity of having a guardian in marriage is basically an agreement of the majority of scholars. One of the reasons for a guardian's reluctance in marrying his child of his own choosing is due to the lack of equality or incompetence between his child and his chosen candidate. Kafāah or kufu, in terms of language can be interpreted as equal, balanced or harmonious. A guardian who does not give permission for his child to marry on the grounds that he is not kafāah is very justified by syara'. However, wali adhol should not be used in any place, meaning that at any time a woman can use this excuse to legalize her marriage. Considering the issue of kafāah in determining the dimensions, it is very abstract, and from a legal point of view it is only a suggestion. The reason for the wali adhol should be an alternative to a very urgent problem. To be careful, then a judge should prohibit the marriage of a woman without the permission of her guardian without urgent reasons, especially if it is just a matter of kafāah.